Study on the Vortex in a Pump Sump and Its Influence on the Pump Unit - Xijie Song; Chao Liu; Zhengwei Wang (Journal of Marine Science and Engineering, 2022)
The vortex in a pump sump is a negative problem for the pump unit, which can lead to the decline of pump performance. Focusing on the internal pressure characteristics of the floor-attached vortex (FAV) and its influence on the pump unit, the FAV was analyzed adopting the previously verified numerical simulation method and experiment. The results show that the pressure in the vortex core gradually decreases with time, drops to a negative pressure at the development stage, and then reaches the lowest pressure during the continuance stage. When the negative pressure of the vortex tube is around the vaporization pressure of the continuance stage, it can cause a local cavitation at the impeller inlet. The evolution of the FAV is accompanied by a change of pressure gradient in the vortex core which is discussed in detail. This research provides theoretical guidance for a better understanding of the vortex characteristics and the optimal design for the pump.